The concept of life (βίος) for Aristotle and its importance in eudaimonist ethics - Alfaro Molina, Juan Gabriel (2022)
A fundamental term in bioethics is bios (βίος), which literally means life, but not life common to all living beings, biological life, but rather the life of rational beings, among whom is God and human beings. humans. Aristotle links this bios with the term of happiness (εὐδαιμονία), since it can correspond to three lifestyles, the hedonic, the political or the contemplative. The main discussion among scholars is whether happiness is exclusive to one of those lifestyles, where the contemplative stands out, or whether it is the amalgamation of all these ways of living. In addition to this, the question arises that regardless of the type of life necessary to be happy, the human being is a being immersed in time and immersed in the swing of destiny, hence a happy life is always in the anxiety that it can cease to be when there is a drastic change in life circumstances. Any turning point in the life of the human being is enough to change the course of his existence.